2021
DOI: 10.1021/acs.chemmater.1c01262
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Tunable Textured Interfacial Defects in PbZrO3-Based Antiferroelectric Perovskite Oxides

Abstract: Antiferroelectric perovskite oxides, which can undergo ultrafast charge/discharge with a large energy storage density, are among the most important functional materials for applications in pulsed power capacitors. Owing to the complex modulation of atomic displacement, a variety of interfacial defects have been observed within a single antiferroelectric domain. However, the intercorrelation between different interfacial defects is still less understood. Here, we report the finding of the evolution of interfaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Corresponding to a larger coercive field and Pmax, the (110)C ori ented film delivers higher energy storage density (Jrec = 21.4 J/cm 3 ) than the other two (Jr ≈ 16 J/cm 3 ) [71]. From a microstructural perspective, one may expect that the type and density of structural defects [116][117][118][119] may influence the energy storage performance Through introducing local compressive pressure, Zhang et al reported that enhanced crit ical fields may increase the Jrec [53,67,120], e.g., from 9 to 16.2 J/cm 3 in Li + -La 3+ co-doped PbZrO3 films. By constructing a ferrielectric (FiE) M2-M3 phase boundary, Luo et al achieved an energy density of 6.3 J/cm 3 with η = 90% in (1-x)AgNbO3-xAgTaO3 solid so lution [46].…”
Section: Anisotropic Energy Storagementioning
confidence: 99%
“…Corresponding to a larger coercive field and Pmax, the (110)C ori ented film delivers higher energy storage density (Jrec = 21.4 J/cm 3 ) than the other two (Jr ≈ 16 J/cm 3 ) [71]. From a microstructural perspective, one may expect that the type and density of structural defects [116][117][118][119] may influence the energy storage performance Through introducing local compressive pressure, Zhang et al reported that enhanced crit ical fields may increase the Jrec [53,67,120], e.g., from 9 to 16.2 J/cm 3 in Li + -La 3+ co-doped PbZrO3 films. By constructing a ferrielectric (FiE) M2-M3 phase boundary, Luo et al achieved an energy density of 6.3 J/cm 3 with η = 90% in (1-x)AgNbO3-xAgTaO3 solid so lution [46].…”
Section: Anisotropic Energy Storagementioning
confidence: 99%
“…It can be clearly observed that with the increase of Sr 2+ content, the interface defects change from neatly arranged stripes to densely scattered spots. From previous studies on interface defects 37 , such an evolution is closely correlated with the degree of A‐site displacement ordering. And the change of order degree is finally reflected in the switching field.…”
Section: Resultsmentioning
confidence: 68%
“…That is, the compensated net zero polarization allows the stable presence of dense translational boundaries; otherwise, the system would have a very high polarization energy with a high density of polar translational boundaries . In comparison, such translational APBs exhibit polarity in PZ, ,, accounting for their lower density as seen in Figure S5. Moreover, the antipolarity of translational APBs may explain their inertial response to external stimuli as they may require a much higher threshold field to break the antiparallel configurations of the translational APB structure.…”
Section: Resultsmentioning
confidence: 99%